APPRAISAL OF THE EMPOWERMENT AND TRAINING PROGRAM IN ACHIEVEING ZAKAT AMIL PERFORMANCE THROUGH ISLAMIC JOB SATISFACTION - Asma Munifatussaidah; Ari Prasetyo (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2023)
Empowerment and training program become a new technique that makes employees proactive in improving their performance. Thus, this research purpose to observe the appraisal of the Employee Empowerment and Training programs of zakat in achieving Employee zakat (Amil) Performance by mediating Islamic Job Satisfaction at the Zakat Institution (LAZNAS) in Central Java. This research used quantitative method with a survey approach. The research sample was 180 Amil at 12 LAZNAS in Central Java, who served in the collection, distribution, and utilization of zakat with a minimum service period of two years, and had received training about zakat management. The research sample was selected through the purposive sampling technique and analyzed with the Partial Least Square (SEM-PLS). The research findings indicate that the variables Employee Empowerment and Training programs have an effect toward Islamic Job Satisfaction. Then there is the direct and indirect effect of the Training programs toward the AmilPerformance at the Zakat Institution (LAZNAS) in Central Java with the mediation of Islamic Job Satisfaction. Meanwhile, for the effect of the Employee Empowerment toward Amil Performance, there is no significant in direct effect. However, there is an indirect effect of the Employee Empowerment toward  Amil Performance at the Zakat Institution (LAZNAS) in Central Java with the mediating Islamic Job Satisfaction. This research was expected to be of particular concern to zakat institutions, especially in the human resources section to help provide information regarding the importance of empowering and training program for Amil performance in Zakat Institutions (LAZNAS) to improve collecting, distributing and utilizing zakat.